2018
DOI: 10.1038/s41467-018-06487-5
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic signaling linked to autophagy enhances host protection against intracellular bacterial infections

Abstract: Gamma-aminobutyric acid (GABA) is the principal inhibitory neurotransmitter in the brain; however, the roles of GABA in antimicrobial host defenses are largely unknown. Here we demonstrate that GABAergic activation enhances antimicrobial responses against intracellular bacterial infection. Intracellular bacterial infection decreases GABA levels in vitro in macrophages and in vivo in sera. Treatment of macrophages with GABA or GABAergic drugs promotes autophagy activation, enhances phagosomal maturation and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 70 publications
4
112
0
1
Order By: Relevance
“…22 GABA signaling promotes autophagy activation, which improves phagosome maturation and promotes host protection against infections. 23 To our knowledge, the beneficial effect of hypnotics on clinical outcome has not been reported previously in the management of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 75%
“…22 GABA signaling promotes autophagy activation, which improves phagosome maturation and promotes host protection against infections. 23 To our knowledge, the beneficial effect of hypnotics on clinical outcome has not been reported previously in the management of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, the activation of GABAergic signaling is positively implicated in the treatment of these conditions, but based to our knowledge, the potential relation of autophagy and GABAergic signaling in inflammatory conditions have not been investigated so far. Besides the role of GABA in the induction of antimicrobial autophagy 18 , our group as well as studies from other groups reported the potential of some Lactobacillus species to stimulate or suppress autophagy [19][20][21] . In addition, the role of autophagy in immunomodulatory effects of GABA-producing probiotic strain have not been investigated.…”
mentioning
confidence: 99%
“…However, the relation between GABA-producing LAB and their immunomodulatory properties has not been investigated previously. Considering recent findings on potential linkage of GABA signaling and autophagy 18 , we hypothesized that the direct immunomodulatory activity of GABA produced by L. brevis BGZLS10-17 include the regulation of autophagy within these immune cells.…”
mentioning
confidence: 99%
“…Additionally, ~25-fold upregulation of GABAergic neurotransmission upon blood feeding in the midgut highlights its possible functionality in the regulation innate immune response by activating the autophagy response as a result of gut flora expansion following blood feeding (Fig. 5d) [61].…”
Section: Fig 4: Innate Physiological Status Differentially Modulatesmentioning
confidence: 97%